Edgar Zilsel ‘The Social Roots of Romantic Ideology’ (1933). A translation and commentary - Scott, Alan (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
Edgar Zilsel (1891-1944) was an associate of the Vienna Circle and an Austro-Marxist. He is remembered for the so-called ‘Zilsel Thesis’, a historical reconstruction of the social and economic preconditions for the emergence of modern experimental science written in exile in the USA. His earlier work in Vienna on the cult of genius has recently been revisited by a number of scholars. The aim of this translation is to make one of his writings on this subject available to an Anglophone audience. Here he develops a genealogy of irrationalist ideology—one opposed to the rationalism of urban and commercial culture and to science—whose roots he traces to the German Romantic Movement. He offers a novel account of the interaction between Romantic writers, artists, and philosophers and wider currents of counter-revolutionary thought that emerged as a reaction to the French Revolution. The commentary seeks to contextualize the work as a critical, if indirect, contemporary engagement with fascism and points to its contemporary relevance.